«Cadornismo politico» e rivoluzione in Occidente. Antonio Gramsci tra Caporetto e Ottobre sovietico - Vander, Fabio (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
Two First World War episodes were particularly formative in Antonio Gramsci’s “political education”: the Bolshevik revolution and the Italian military defeat in Caporetto. Gramsci realizes the need of a new link between attack and defense, war of movement and of position. The essay investigates the strategic innovations induced in European political thought with the First World War and with Giulio Douhet’s theses and their consequences in Gramscian and Communist thought of the same period. Keywords: War of movement/war of position; Gramsci; Trotski; Western Revolution.